2020
DOI: 10.1308/rcsfdj.2020.111
|View full text |Cite
|
Sign up to set email alerts
|

Health and wellbeing

Abstract: In these times of change and uncertainty, it has never been more important to be aware of our health and keeping emotionally resilient. Dental professionals are notoriously a difficult to reach group when it comes to individual healthcare and seeking help. COVID-19 has hit dentistry and the dental profession hard, in a way we could never have expected. Everyone has been subject to changes that could not have been contemplated. Each person on the planet has been impacted in one way or another. Maybe because we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…DiDs are normally unaware of how to move forwards once the GDC has summoned them to a FtP and they seek what help is available 10,11,13,[18][19][20]22,24,25,26,28,29,30,31,32 . It has been reported that dentists find themselves in circumstances that lead to misguided decisions and like "The Swiss cheese model" they fall through the holes 12,15,17 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…DiDs are normally unaware of how to move forwards once the GDC has summoned them to a FtP and they seek what help is available 10,11,13,[18][19][20]22,24,25,26,28,29,30,31,32 . It has been reported that dentists find themselves in circumstances that lead to misguided decisions and like "The Swiss cheese model" they fall through the holes 12,15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…culture, patient factors and poor work-life balance) 10,11,12,13,15,16,17,18,19,22,24,25,26,34,35,36,37 . This is reported as highly emotional with associated mental health issues 1,2,3,4,6,7,8,12,13,16,17,18,22,28,29,35 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations